2011
DOI: 10.1007/s11191-011-9379-7
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Molecular Mechanisms: A Framework of Scientific Reasoning to Construct Molecular-Level Explanations for Cellular Behaviour

Abstract: Although molecular-level details are part of the upper-secondary biology curriculum in most countries, many studies report that students fail to connect molecular knowledge to phenomena at the level of cells, organs and organisms. Recent studies suggest that students lack a framework to reason about complex systems to make this connection. In this paper, we present a framework that could help students to reason back and forth between cells and molecules. It represents both the general type of explanation in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(108 citation statements)
references
References 66 publications
3
105
0
Order By: Relevance
“…The design presented in this paper builds on the theoretical analysis presented previously by Van Mil et al (2013) and is informed by empirical evidence from one previous research cycle with a similar setup to the case study presented here. To be able to determine whether the design was indeed a proof of principle, we first describe and justify the features that we incorporated into the design and explain how we expected these principles to shape and guide the learning process.…”
Section: Research Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…The design presented in this paper builds on the theoretical analysis presented previously by Van Mil et al (2013) and is informed by empirical evidence from one previous research cycle with a similar setup to the case study presented here. To be able to determine whether the design was indeed a proof of principle, we first describe and justify the features that we incorporated into the design and explain how we expected these principles to shape and guide the learning process.…”
Section: Research Strategymentioning
confidence: 99%
“…The upward question: "What is its role or function, or how does it contribute to the larger whole?" Figure 2 is a schematic representation of the general mechanistic reasoning structure (adapted from Van Mil et al, 2013). The structure directs one to search for relationships between entities and activities at different levels (parts and wholes), as well as to search for causal connections within one level (cause and effect).…”
Section: Tapping Into Students' Mechanistic Intuition To Place Proteimentioning
confidence: 99%
“…The heuristic guiding our decision here was that levels should be added when the new ideas are directly related to the construct, represent an important conceptual shift, and/or afford instructional leverage. Given that the transition from a non-information-based to an information-based view of genes is a particularly challenging one (Duncan & Reiser, 2007;Lewis & Kattmann, 2004;van Mil, Boerwinkel, & Waarlo, 2011;Venville & Treagust, 1998), we decided that capturing this understanding as a distinct and separate level was merited. Cognitively speaking, this understanding reflects an ontological shift in students' understandings of genes, in essence the beginning of an important conceptual change (Venville & Treagust, 1998 recognize this understanding as bridging across ontologically distinct understandings of genes and leverage it in their instruction.…”
Section: Refining the Levels Of An Lpmentioning
confidence: 99%
“…Together, these issues make the learning of cell biology rather uninspiring for students. Moreover, previous studies have reported that students fail to make connections across different topics, leading them to only partially appreciate how nature functions (Mil, Boerwinkel, and Waarlo 2011;Newman, Catavero, and Wright 2012). From my previous experience, I have noted that students tend to study topics in isolation, with little or no regard for functional interactions among them.…”
Section: Introductionmentioning
confidence: 96%